Distribusi dan Analisa Kekerabatan Padina sp dari Perairan Pulau Lombok Berdasarkan Karakter Morfologi - Ghazali, Mursal; Nurhayati, Nurhayati; Suripto, Suripto; Sukenti, Kurniasih; Julisaniah, Nur Indah (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Padina sp is a member species of brown macroalgae that produces alginat. In general, Padina sp grows scattered from the intertidal zone to the subtidal zone. The difference in environmental conditions certainly has an impact on the morphological variations of plants, including Padina sp. This study aims to examine the distribution of Padina sp growing in the waters of Lombok Island, as well as the kinship based on morphological characters. Sampling was conducted in 18 locations spread across 3 districts, namely: West Lombok Regency, Central Lombok Regency, and East Lombok Regency. Sampling was carried out at the place where Padina sp was grown in its intact form and was still alive. Furthermore, the obtained Padina sp. Was documented and characterized morphologically. The morphological characterization data were used to calculate the level of equality between chrysanthemum cultivars (OTU) (Matrix Similarity), and to compile dendrograms through cluster analysis using the MVSP 3.1 (Multi Variate Statistical Package Version 3.1) program. The results showed that, of the 18 sampling locations, Padina sp was found in 15 locations. The morphological variation is relatively high, which is divided into 4 major groups. Padina sp from Malimbu is the species with the smallest similarity index.